Pemanfaatan Limbah Bawang Merah sebagai Pupuk pada Pekarangan Rumah bagi Buruh Pengupas Bawang Merah di Nagari Muaro Paneh - Helmi, Dewilna; Asep, Asep; Ansiska, Paisal; Partini, Dwi; Barus, Celsia (Universitas Pattimura, 2023)
Solok Regency is the largest shallot producing district in West Sumatra Province. The abundant harvest has had a positive impact on housewives who do not work by becoming daily laborers peeling shallots. Peeled red onions produce abundant waste, the use of which has not been optimized. There are various benefits contained in shallots which are useful for plant growth, this is based on previous research that has been carried out. Organic fertilizer can be produced by utilizing shallot waste. The aim of Community Service (PKM) activities is to provide additional knowledge to the community in utilizing shallot waste into organic fertilizer that can be used for home garden plants. The target of this activity is housewives who are daily laborers for peeling shallots, totaling 25 people. This PKM activity consists of stages of observation, socialization, discussion and evaluation. The service activities took place during July 2023. The results of this activity were 1) participant participation in attendance reached 92% and participant activeness reached 80%, 2) participants' understanding in following the material reached 84%, 3) participants' skills in processing shallot waste amounted to 80%.